Pengaruh Gaya Kepemimpinan Syura terhadap Motivasi dan Prestasi Belajar Siswa - Lulu Andiani; Nurafilah Pebriyanti; Tiara Dewi Lestari; Yayu Nuraidah Solihat (Jurnal Pendidikan Indonesia (JOUPI), 2024)
Leaders play a crucial role in the outcomes achieved by an organization. In education, for example, schools need principals or leaders who can guide educators and students towards achieving the school's vision and mission. However, in today's era, leadership often becomes just a title without considering the leadership style that influences subordinates. To address this, a deeper understanding of leadership styles, such as the syura leadership style, is necessary. The syura leadership style, which emphasizes the principles of deliberation and active participation of all members, is seen as a potential approach to creating a conducive learning environment. This study aims to analyze the influence of the syura leadership style on students' motivation and academic achievement. The research method used is a qualitative and descriptive approach. The results of the study show that the syura leadership style has a positive and significant impact on students' learning motivation. Additionally, high learning motivation also significantly contributes to the improvement of academic achievement. Overall, these findings indicate that the implementation of the syura leadership style in school environments can enhance students' motivation and academic performance. This study suggests that educators and school leaders consider adopting the syura leadership style to create a more inclusive and participatory learning environment, in order to achieve optimal educational outcomes.